STIMULATING SUSTAINABLE CONSUMPTION THROUGH SOCIAL AND ENVIRONMENTAL BUSINESS BEHAVIOR: AN STUDY IN WALMART BRAZIL - Minelle Enéas da Silva (Revista Metropolitana de Sustentabilidade, 2013)
Under a market dynamic current, increasingly new behaviors of business are required in relation to the social and environmental aspects. Thus, considering the emergence of a new consumption paradigm, this paper aims to identify how a social and environmental behavior of Wal-Mart Brazil can be stimulating an effective sustainable consumption in the supermarket retail. According to this idea, this research had a qualitative approach and was conducted by a case of study, in which we identified that with an incorporation of responsible practices exist a stimulus to sustainable consumption in the retail studied, in order to a new behavior in the company. For this, we can identify that was necessary a set of social interactions that contribute with a different perspective.